Innovation under Constraint: Social Entrepreneurship Models in Geographically Isolated Communities - Chenda Dara; Dara Vann; Vicheka Rith; Dodi Setiawan Riatmaja (Pengabdian: Jurnal Abdimas, 2026)
Background. Geographically isolated communities face persistent structural constraints that limit access to resources, markets, and institutional support. However, these challenging conditions also act as a generative environment, fostering unique forms of innovation deeply embedded within local contexts. Purpose. This study aims to examine the development and sustainability of social entrepreneurship models under resource constraints. It specifically focuses on adaptive strategies, governance structures, and the processes of resource mobilization within these isolated settings. Method. The study employed a qualitative multiple-case study design, analyzing twelve social enterprises across the agriculture, education, and healthcare sectors. The research combined descriptive and inferential analysis to identify recurring patterns of innovation and organizational sustainability. Results. Findings indicate that innovation in these communities emerges through hybrid resource configurations, robust community engagement, and the integration of local knowledge systems. Furthermore, the evidence shows that participatory governance significantly strengthens organizational resilience, proving that constraints can drive sustainable entrepreneurial practices rather than just limiting them. Conclusion. The study concludes that social entrepreneurship in isolated areas requires a shift in innovation frameworks prioritizing relational dynamics, adaptability, and local agency over traditional metrics like scalability and resource abundance. These insights offer a foundation for designing development interventions that are contextually grounded and sensitive to local realities.